A Cross-Cultural Validation of the Tourism Web Acceptance Model (T-WAM) in Different Cultural Contexts. Issue 3 (26th May 2016) - Besbes, Alia; Legohérel, Patrick; Kucukusta, Deniz; Law, Rob
ABSTRACT: Internet use has intensified worldwide. However, this evolution masks cultural differences in booking behaviors. This study investigates the effects of culture on the online booking practices of consumers from Tunisia and China. Differences in the structural patterns across the Tunisian (Arabic) and Chinese (Asian) cultural contexts are analyzed. We find that the model of technology acceptance for tourism online booking (tourism web acceptance model) holds for both countries. The effects of perceived risk or subjective norms, which are highly significant in the Tunisian context, attest to the important influence of culture on the online booking behaviors of consumers. Two cognitive constructs, namely, perceived usefulness and perceived ease of use, produce a greater effect on the online booking behaviors of those from Tunisia.